Anthropological approaches to the study of religion - Banton, Michael, 1926-2018 (Routledge library editions. Anthropology and ethnography., 2004)
As the basic questions of social structure were elucidated there came a quickening of interest among social anthropologists in the study of religion. Chapters in this book include: · Religion as a Cultural System (Clifford Geertz) · Colour Classification in Ndembu Religion (Victor W. Turner) · Religion: Problems of Definition and Explanation (Melford E. Spiro) · Fathers, Elders and Ghosts in Edo Religion (R.E. Bradbury) · Territorial Groupings and Relgion among the Iraqw (Edward H. Winter). First published in 1966.